Asesmen Transformasi Digital Galeri Nasional Indonesia - Sari, Desy Novita; Wijayanti, Luki (UI Scholars Hub, 2023)
Digital transformation assessment has not received full attention and is still rarely carried out by art galleries/museums in Indonesia. Digital transformation research on library and information science (LIS) that covers GLAM's concept focuses more on libraries, archives, and museums, while art galleries are scarce, especially in Indonesia. This study aims to conduct a digital transformation assessment of art galleries, especially the National Gallery of Indonesia (Galnas). The research uses a quantitative method by applying a digital transformation framework questionnaire that had tested at 400 cultural institutions in Italy (including art galleries). This research measures the Digital Readiness Index (DRI) on five dimensions: people, technology, processes, customers, strategy and investment. Interviews with Galnas managers had conducted to confirm the questionnaire’s answers. The results showed that the DRI value of the strategy and investment dimensions was 0.59; technology 0.22; people 0.14; processes and customers each 0.07. The overall level of digital readiness for Galnas is low.